2017
DOI: 10.3758/s13423-016-1220-5
|View full text |Cite
|
Sign up to set email alerts
|

A locus coeruleus-norepinephrine account of individual differences in working memory capacity and attention control

Abstract: Studies examining individual differences in working memory capacity (WMC) have suggested that low WMC individuals have particular deficits in attention control processes compared to high WMC individuals. In the current article we suggest that part of the WMC-attention control relation is due to variation in the functioning of the locus coeruleus-norepinephrine system (LC-NE). Specifically, we suggest that because of dysregulation of LC-NE functioning, the fronto-parietal control network for low WMC individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
228
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 171 publications
(259 citation statements)
references
References 235 publications
29
228
2
Order By: Relevance
“…People who experienced more fluctuations in arousal performed worse on the task, and people who allocated more attention toward maintaining the items during the delay intervals performed better on the task. These findings are in line with prior theorizing about individual differences in the functioning of the LC-NE system in the service of attention and WM (Unsworth & Robison, 2017a, 2017b. We have argued that stability and consistency of delivery of NE to the frontal cortices by the LC is an important underlying factor in why people vary in their ability to control their attention and effectively utilize their limited WM system.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…People who experienced more fluctuations in arousal performed worse on the task, and people who allocated more attention toward maintaining the items during the delay intervals performed better on the task. These findings are in line with prior theorizing about individual differences in the functioning of the LC-NE system in the service of attention and WM (Unsworth & Robison, 2017a, 2017b. We have argued that stability and consistency of delivery of NE to the frontal cortices by the LC is an important underlying factor in why people vary in their ability to control their attention and effectively utilize their limited WM system.…”
Section: Discussionsupporting
confidence: 89%
“…Indeed, we have argued that variation in the consistent functioning of the LC-NE system underlies individual differences in WM capacity and attention control abilities (Unsworth & Robison, 2017a), and we have demonstrated that variation in pretrial and task-evoked pupil diameter during attention control tasks correlates with individual differences in WM capacity, attention control abilities, and the tendency to mind-wander during such tasks (Unsworth & Robison, 2017b). Therefore, both pretrial pupil diameter and task-evoked pupil diameter may potentially measure fluctuations in performance in a WM task.…”
Section: Fluctuations In Working Memorymentioning
confidence: 99%
“…The locus coeruleus serves as the brain's hub region for integrating signals about arousal (Mather, in press-b) and is believed to play a key role in modulating how focused attentional processes are on motivationally-relevant stimuli Mather et al, 2016;Nieuwenhuis, Gilzenrat, Holmes, & Cohen, 2005;Unsworth & Robison, 2017;Waterhouse & Navarra, 2019). Theoretical models propose that attentional selectivity for salient or high priority stimuli is particularly robust under conditions of increased phasic LC activity (e.g., Mather et al, 2016), which primarily emerge when tonic levels of LC activity are reduced .…”
Section: Discussionmentioning
confidence: 99%
“…Baseline PD in typically developed adults was positively correlated with fluid intelligence and attentional control (Tsukahara et al ., ). This interrelation was explained by enhanced functional network connectivity via increased tonic LC–NE activity (Hermans et al ., ; Unsworth & Robison, ). Individual set points represented an intrinsic or net alertness that was reflected by baseline PD (Sturm & Willmes, ).…”
Section: Lc–ne Moderating Attentional Function and Pupil Dilationmentioning
confidence: 99%